From weather to wallet: Evidence on seasonal temperature shocks and global food prices - Elisabeth Falck; Patrick Schulte (Deutsche Bundesbank, 2025)
In this paper, we provide evidence on the impact of global seasonal temperature shocks on global food commodity prices. Utilizing monthly data from 1961 to 2023, we find an economically and statistically highly significant, longer-lasting positive impact of summer temperature shocks on global food commodity prices. In contrast, we do not find such effects for winter, spring or autumn temperature shocks. A summer which is 0.4 êC hotter than in the previous five years, roughly equal to the largest summer shock we observe in our sample, causes food commodity prices to rise by about 10 % within 12 months. In addition, we show that such weather shocks lower global food production quantities, indicating that such shocks can be classified as supply shocks.
Keywords: Q02; Q11; E31; 330; Global seasonal temperature shocks; food commodity prices; food production; local projections